The Benefits of Early Mobilization on Post-Abdominal Surgery: A Review of Literature - Juita Juita; Sri Yona; Riri Maria (UIMA Press, 2023)
Background: post-abdominal surgery and postponed physical recovery are significant problems. Thus, early mobilization is important to treat the post-surgical procedure, facilitate recovery, and prevent further complications. Objectives: this literature review was to find the benefits of early mobilization on post-abdominal surgery. Methods: the researchers took the data from PubMed, EBSCOhost, ProQuest, Science Direct, and Scopus, published from 2017-2022 with the predetermined keywords. The searching method applied the Prefered Reporting Items for Systematic Review and Meta-Analysis, PRISMA guideline. The researchers conducted the research in November 2022. Articles selected with criteria for publication in International Journals within the last five years, in English, using experimental research designs, randomized controlled trials (RCTs), quasi-experiments, and cohort studies. Results: the researchers found 57.990 articles from various data sources. They were Pubmed (n = 43), EBSCOHost (n = 1.223), Science Direct (n = 325.800), ProQuest (n=30.279), and Scopus (n=645). After promoting the first screening step, the researchers eliminated some obtained journal articles. The only articles published within five recent years with full-text conditions were 162 articles. Then, the researchers screened the articles based on the second and third criteria: having open access and writing in English. The results were 10 articles. Then, the researchers checked the duplications and screened the titles and the abstract, resulting in six articles. The results showed that the analyses of six articles stated that early mobilization, from the post of day 0 or 24 hours after the abdominal surgery could improve the respiratory function with SpO2 and SaO2 increase. The mobilization could also reduce the length of stay and make the cost more efficient. Conclusion: The mobilization provided many advantages to reducing post-abdominal surgery complications, morbidity, and mortality.